EXPLORING LIPID-BASED DRUG DELIVERY IN CANCER THERAPY VIA LIPOSOMAL FORMULATIONS - RODRIQUES, PAUL; THACKER, KRUPALI; BHUPENDRA G, PRAJAPATI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
In many countries across the world, cancer is a leading cause of death. Cancer is the biggest cause of death worldwide, with approximately 10 million fatalities expected in 2020, accounting for nearly one in every six deaths. Mutations in ~300 human genes can unleash cell division, potentially leading to cancer. The effectiveness of existing conventional therapies for a number of cancers is, however, inefficient in terms of safety and efficacy. Medication systems based on lipid can be configured to treat tumors passively with increasing safety by reducing toxicity and increasing efficacy by target drug delivery. Lipid-based drug dosage form is the new identified technological design to overcome problems such as water-soluble solubility and bioavailability. A wide range of product specifications determined by indication of disease, route of administration, price evaluation, safety, toxicity, and efficiency could be customized to lipid formulations. This analysis explores the current state of lipid drug delivery studies, including the production of cancer liposomes, different cancer-focused strategies, and liposomal formulation of numerous anti-cancer drugs.